Comparison Effectiveness of Antidiabetic Activity Extracts of Bay Leaves (Syzygium polycephalum) and Moringa Seeds (Moringa oleifera L.) - Trini Suryowati; Sealtiel Bombing Rombelayuk Allorante; Achnes Pangaribuan (CV. Inara, 2025)
The present study reports a comparative evaluation of the antidiabetic potential of ethanol extracts from Syzygium polyanthum (bay leaves) and Moringa oleifera L. (moringa seeds) based on their inhibitory activity against the α-glucosidase enzyme. Diabetes mellitus, a chronic metabolic disorder characterized by hyperglycemia due to impaired insulin secretion or action, can be managed through enzyme inhibition that delays carbohydrate hydrolysis. The investigation was conducted for five weeks using an in vitro experimental method, in which both plant materials were extracted via maceration with 70% ethanol. The α-glucosidase inhibition assay was performed spectrophotometrically at 410 nm, and the half-maximal inhibitory concentration (IC₅₀) was determined to compare the inhibitory capacities of both extracts. Phytochemical profiling revealed that bay leaf extract contains flavonoids, tannins, saponins, and steroids, while moringa seed extract contains flavonoids, alkaloids, and steroids. Results showed that bay leaf extract exhibited strong α-glucosidase inhibition with an IC₅₀ value below 100 ppm, indicating a significant potential as a natural antidiabetic agent. In contrast, moringa seed extract demonstrated weaker activity with no substantial inhibition observed at the tested concentrations. Based on comparative analysis, bay leaf extract shows a higher inhibitory efficiency, suggesting its potential application in herbal antidiabetic formulations. Further studies are recommended to explore the optimal concentration range and bioactive constituents of moringa seeds.